Harmonic Bernoulli strings and random permutations - Eugenius Manstavičius (Lietuvos Matematikos Rinkinys)
We examine fairly special b-harmonic Bernoulli strings appearing in n observations. It is shown that their count number can be used to define a random process converging to the Brownian motion as n tends to infinity. The proof is based upon the invariance principle for random permutations.